Dinamika Islamisasi dan Peran Pemikiran Muhammad Basiuni Imran di Sambas, Kalimantan Barat - Haif, Abu; Sabari Sabari; Zulfikar Ghazali (Pusat Riset dan Inovasi Nasional, 2026)
Islamization in Sambas, West Kalimantan, represents a historical and evolving process influenced by trade routes, the political dynamics of local kingdoms, and the transmission of Islamic knowledge through networks of scholars and local intellectuals. This process extended beyond the mere dissemination of religious teachings, encompassing significant social, cultural, and educational transformations within the community. A central figure in this Islamization process was Muhammad Basiuni Imran (1885–1976), the Maharaja Imam of the Sambas Sultanate, who played a pivotal role in reforming Islamic education and strengthening religious understanding among the local population. This article employs a historical-qualitative approach and library research to trace the trajectory of Islamization in Sambas while analyzing Basiuni Imran’s contributions within the socio-cultural context of the region. The findings reveal that Basiuni Imran’s thought reinforced Islamization through the modernization of Islamic education, the integration of Sharia with local customs, and the establishment of adaptive religious structures, thereby significantly shaping the religious life of the Sambas community from the colonial period to the early years of Indonesia’s independence.